2003
DOI: 10.1002/elps.200305449
|View full text |Cite
|
Sign up to set email alerts
|

Separation of aminoalkanephosphonic acid enantiomers by indirect UV detection capillary electrophoresis with application of cyclodextrins

Abstract: Indirect UV detection capillary electrophoresis (CE) was used for the separation of aminoalkanephosphonic acid (AP) enantiomers by applying commercially available cyclodextrins as chiral discriminators. The results show that the separation of the enantiomers depends on pH of the background electrolyte, the molar ratio of cyclodextrin to aminophosphonic acid, and on the type of the applied chiral selector. Optimization of process conditions allowed enantiomeric baseline separation or partial separation of 12 ou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 23 publications
0
8
0
Order By: Relevance
“…It was shown that, heptakis(2,6-O-dimethyl)--CD [108], heptakis(2,6-O-dimethyl)--CD [107] as well as another derivatives of CDs such as acetylated--CD [129] and hydroxypropyl analogues of -, -and -CDs [107,108,110] create stereospecifically inclusion complexes with structurally variable aminophosphonates. Thus, they were successfully applied as chiral additives in high performance liquid chromatography [129], capillary electrophoresis [107,108] and NMR spectroscopy [110] for enantiodiscrimination of aminophosphonic and aminophosphinic acids and their derivatives.…”
Section: Functionalized Cyclodextrinsmentioning
confidence: 99%
See 1 more Smart Citation
“…It was shown that, heptakis(2,6-O-dimethyl)--CD [108], heptakis(2,6-O-dimethyl)--CD [107] as well as another derivatives of CDs such as acetylated--CD [129] and hydroxypropyl analogues of -, -and -CDs [107,108,110] create stereospecifically inclusion complexes with structurally variable aminophosphonates. Thus, they were successfully applied as chiral additives in high performance liquid chromatography [129], capillary electrophoresis [107,108] and NMR spectroscopy [110] for enantiodiscrimination of aminophosphonic and aminophosphinic acids and their derivatives.…”
Section: Functionalized Cyclodextrinsmentioning
confidence: 99%
“…Thus, they were successfully applied as chiral additives in high performance liquid chromatography [129], capillary electrophoresis [107,108] and NMR spectroscopy [110] for enantiodiscrimination of aminophosphonic and aminophosphinic acids and their derivatives. Mixture of sulfated CDs was reported to form diastereomeric transient complexes with enantiomers of 1,1'-binaphtyl-2,2'-diylhydrogen phosphate in capillary zone electrophoresis [130].…”
Section: Functionalized Cyclodextrinsmentioning
confidence: 99%
“…High-performance liquid chromatography on chiral columns [17,18] and capillary electrophoresis using quinine [19] or cyclodextrins [20,21] as chiral discriminators have also been used for the analysis of enantiomeric composition of chiral aminophosphonic acids. Derivatization of aminophosphonates is a necessary procedure to analyze compounds by gas chromatography methods (either alone or coupled with mass spectrometry).…”
Section: Physical/chemical Properties and Analysismentioning
confidence: 99%
“…Over the last decade, capillary electrophoresis (CE) has proved powerful for separating analytes ranging from small molecules to macromolecules as a result of its extremely high separation efficiency, very short analysis time, and a requirement for only small volumes of sample. Among different CE approaches, capillary zone electrophoresis (CZE) with indirect UV detection is the most universal and efficient method for determination of nonabsorbing analyte compounds [5][6][7][8][9][10][11][12][13][14][15]. Detection of migrating sample ions is generally achieved by the displacement of the probe ions (co-ions; chromophores) in the running buffer.…”
Section: Introductionmentioning
confidence: 99%
“…This causes a negative peak when such anions pass through the detector and the peak area of the resulting negative peak is used for quantification of the analytes. Despite its popularity, indirect UV absorbance suffers mainly from a lack of selectivity and detection limits are commonly in the submilli to micromolar range (10 −4 to 10 −6 M) [5][6][7][8][9][10][11][12][13][14][15]. Several other detection methods have been reported for the determination of small phosphorus-containing compounds, such as laser-induced fluorescence (LIF), indirect LIF, electrochemical, and direct UV detection modes.…”
Section: Introductionmentioning
confidence: 99%